LISA: the Italian CRG beamline for x-ray Absorption Spectroscopy at ESRF. (May 2016) - d'Acapito, F.; Trapananti, A.; Puri, A.
Abstract: LISA is the acronym of L inea I taliana per la S pettroscopia di A ssorbimento di raggi X (Italian beamline for X-ray Absorption Spectroscopy) and is the upgrade of the former GILDA beamline installed on the BM08 bending magnet port of European Synchrotron Radiation Facility (ESRF). Within this contribution a full description of the project is provided.